2023
DOI: 10.1098/rspb.2023.0404
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cryptic sex in parthenogenetic stick insects of the genus Timema

Susana Freitas,
Darren J. Parker,
Marjorie Labédan
et al.

Abstract: Obligately parthenogenetic species are expected to be short lived since the lack of sex and recombination should translate into a slower adaptation rate and increased accumulation of deleterious alleles. Some, however, are thought to have been reproducing without males for millions of years. It is not clear how these old parthenogens can escape the predicted long-term costs of parthenogenesis, but an obvious explanation is cryptic sex. In this study, we screen for signatures of cryptic sex in eight populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The evolutionary persistence of parthenogenesis has long been discussed (Judson & Normark 1996, Schurko et al 2009), and recent studies have shown evidence of occasional sexual reproduction in the parthenogenetic species that were thought to have reproduced solely parthenogenetically for millions of years (Vakhrusheva et al 2020, Boyer et al 2021, Freitas et al 2023) (but see [Kearney et al 2022]). Therefore, obligately parthenogenetic species with a long history may still have the possibility of utilizing or returning to sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The evolutionary persistence of parthenogenesis has long been discussed (Judson & Normark 1996, Schurko et al 2009), and recent studies have shown evidence of occasional sexual reproduction in the parthenogenetic species that were thought to have reproduced solely parthenogenetically for millions of years (Vakhrusheva et al 2020, Boyer et al 2021, Freitas et al 2023) (but see [Kearney et al 2022]). Therefore, obligately parthenogenetic species with a long history may still have the possibility of utilizing or returning to sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…All these results strongly suggest that R. mikado could no longer return to sexual reproduction. Although not easy to verify, the plasticity of reproductive modes is critical to explain how old or ancient parthenogenetic lineages can avoid the long-term costs of asexuality (Boyer et al 2021, Freitas et al 2023). In this mean, the present study provided unique insights into the evolution and the consequence of the loss of sex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations